Infant Feeding Practices and Perceived Optimal Breastfeeding Interventions among Low-Income Women Delivering at a Baby-Friendly Hospital - Lewkowitz, Adam K.; Raghuraman, Nandini; López, Julia D.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2019)
Objective To determine infant feeding practices of low-income women at a Baby-Friendly Hospital and to ascertain breastfeeding interventions they believe would increase exclusive breastfeeding.Study Design This cross-sectional study occurred at a tertiary care Baby-Friendly Hospital. Low-income women without breastfeeding contraindications were recruited at scheduled obstetrician/gynecologist appointments within 6 to 9 months of delivering a term, nonanomalous infant. Participants completed a survey. Outcomes included infant feeding patterns and perceived usefulness of proposed breastfeeding interventions.Results Of 149 participants, 129 (86.6%) initiated breastfeeding; by postpartum day 2 (PPD2), 47 (31.5%) exclusively breastfed, 51 (34.2%) breastfed with formula, and 51 (34.2%) exclusively formula fed. On a scale of 1 (“strongly agree”) to 5 (“strongly disagree”), women who supplemented with formula on PPD2 were significantly more likely than those who exclusively formula fed to agree education on neonatal behavior, 1 (interquartile range [IQR] 1, 2) versus 2 (IQR 1, 3); p = 0.026 and on-demand access to breastfeeding videos on latch or positioning, 1 (IQR 1, 2) versus 2 (IQR 1, 3), p = 0.043; 1 (IQR 1, 2) versus 2 (IQR 1, 3), p = 0.021, respectively, would have helped them exclusively breastfeed.Conclusion Though low-income women at a Baby-Friendly Hospital had high breastfeeding initiation rates, the majority used formula by PPD2. To increase breastfeeding rates among low-income women, future interventions should provide appropriate and effective breastfeeding interventions.
Keywords: Baby-Friendly Hospital initiative; breastfeeding; breastfeeding educational interventions; health disparity; low-income women